Library Promotion and User Engagement in Pandemic Times: The Case of Kazakhstan (presentation) - Yap, Joseph Marmol (Дніпровський національний університет залізничного транспорту імені академіка В. Лазаряна, 2020)
EN: Objectives. In these trying times due to the global effect of pandemic, what social media accounts do academic libraries in Kazakhstan maintain and how can they improve their social media engagement to continuously connect with their stakeholders? This report provides an overview of the current status of social media engagement of select academic libraries in Kazakhstan during the COVID-19 crises. This paper will give us a picture about the kinds of online postings shared by these libraries particularly with the use of Facebook. Methods. The top two universities ranked by Independent Quality Assurance Agency (IQAA) were considered in this report to compare with the only autonomous organization of education in Kazakhstan. The library social media accounts of these three organizations were investigated to review the number of followers, frequency of posting, and its overall social media engagement. Data collected is publicly available to all potential users, followers, or subscribers. Using the post engagement rate (PER) formula introduced by Socialbakers (2013) and adapted by Peñaflor (2018) & Magno (2016), this report identifies and analyzes the average PER Facebook pages maintained by academic libraries. The engagement metrics looked into the number of interactions and the widest reach possible in every post. All three academic libraries investigated maintain a Facebook page. The other account was just created last February 2020. To compare Facebook data during the pandemic times, public information available from June – August 2020 were measured. Results and Discussion. The social media platforms operated by the academic libraries in Kazakhstan are Facebook, Twitter, Instagram, VK, and YouTube. One of the earliest academic library Facebook accounts established in Kazakhstan started in 2010 with less than 3,000 accumulated followers after ten years. This shows a very slow rise in the number of followers considering an academic population of more than 5, 000 people in 2020. Data revealed that Eurasian National University Library’s Facebook account had a higher PER of 0.83 even if it only debut in 2020 compared to the Facebook page of Nazarbayev University which garnered 0.22 PER. KAZNU Library’s Facebook page had the highest PER of 1.02. Conclusions. Facebook is the most popular social media platform across the globe but it is not the case in Kazakhstan. Library marketing and promotion in Kazakhstan needs to be addressed as public relations is not the primary focus. The utilization of social media as a tool for user engagement is not fully developed. One way to look at it is to consider library staffing and identify their marketing background. The pandemic situation must be the turning point of academic libraries to enhance their reach with their stakeholders. It was a test to know the readiness of the library in terms of online communication and interaction.

UK: Введення. Облікові записи у яких соціальних мережах підтримують академічні бібліотеки в Казахстані у ці важкі часи через глобальну пандемію та як вони можуть покращити свою залученість до соціальних мереж, щоб постійно спілкуватися зі своїми користувачами? Ця доповідь містить огляд поточного стану використання соціальних мереж академічними бібліотеками Казахстану під час кризи COVID-19 та дає нам уявлення про види публікацій в Інтернеті, які публікують ці бібліотеки, особливо у Facebook. Методика. У доповіді розглянуто два найкращих університети в рейтингу Незалежної агенції забезпечення якості освіти (IQAA), щоб порівняти їх з єдиною автономною організацією освіти в Казахстані. Облікові записи цих трьох організацій у соціальних мережах досліджувались з метою перевірки кількості підписників, частоти публікацій та їх загальної залученості до соціальних мереж. Зібрані дані є загальнодоступними для всіх потенційних користувачів, послідовників або підписників. Використовуючи формулу розрахунку коефіцієнту залученості публікації (PER), представлену компанією Socialbakers (2013) та адаптовану Peñaflor (2018) і Magno (2016), у цій доповіді визначено та проаналізовано середні показники коефіцієнту залученості публікацій на сторінках у Facebook, які ведуть академічні бібліотеки. Метрики залучення враховуватимуть кількість взаємодій та найбільше охоплення у кожному дописі. Усі три досліджені академічні бібліотеки ведуть обліковий запис Facebook. Один обліковий запис був створений лише у лютому 2020 року. Тому для порівняння даних Facebook за часів пандемії проаналізувано загальнодоступну інформацію, викладену з червня по серпень 2020 року. Результати та їх обговорення. Платформами соціальних мереж, якими користуються академічні бібліотеки Казахстану, є Facebook, Twitter, Instagram, VK та YouTube. Один з найдавніших бібліотечних облікових записів у Facebook, створений у Казахстані, розпочав свою діяльність у 2010 році і через десять років накопичив менше ніж 3000 підписників. Це свідчить про дуже повільне зростання кількості послідовників, враховуючи академічну чисельність населення понад 5000 осіб у 2020 році. Дані показали, що обліковий запис Євразійського національного університету у Facebook мав вищий показник коефіцієнту залученості публікацій, 0,83, незважаючи на те, що його було започатковано лише в 2020 році порівняно з сторінкою Назарбаєв університету у Facebook, яка набрала 0,22%. Сторінка у Facebook бібліотеки КазНУ мала найвищий показник залученості публікацій – 1,02. Висновки. Facebook – найпопулярніша платформа соціальних мереж у всьому світі, але в Казахстані це не так. Бібліотечний маркетинг та просування бібліотечних послуг в Казахстані потребують вирішення, оскільки зв’язки з громадськістю не є головним напрямком роботи. Соціальні мережі як інструмент залучення користувачів ще не повністю використовуються. Один із методів вирішення цього питання – це розглянути штат бібліотеки та визначити його маркетинговий досвід. Ситуація з пандемією має стати поворотним пунктом для академічних бібліотек, спонукати їх до розширення охоплення більшої кількості користувачів. Це був тест на готовність бібліотек з точки зору онлайн спілкування та взаємодії.
Популяризація бібліотек та залучення користувачів у пандемічні часи: приклад Казахстану (презентація)
J. M. Yap: ORCID 0000-0002-7852-1047
Keywords: social media; user engagement; academic libraries; pandemic; COVID-19; Facebook; Kazakhstan; соціальні мережі; залучення користувачів; академічні бібліотеки; пандемія; Казахстан